Antibacterial Effect of Silver Nanoparticles along with L-Arginine against P. aeruginosa - Mina Parsa; Malahat Ahmadi; Habib Dastmalchi; Aliasghar Tehrani (Medical Laboratory Journal, 2017)
ABSTRACT Background and Objectives: Nowadays, the prevalence of multidrug-resistant pathogens such as Pseudomonas aeruginosa is increasing worldwide. Many studies have been seeking new treatment strategies to treat infections caused by these microorganisms. Silver nanoparticles (AgNPs) along with L-arginine have significant antimicrobial effects and could be used as alternatives for ineffective drugs. Methods: In this study, the antibacterial activity of AgNPs, L-arginine and various concentrations of AgNPs along with L-arginine (12.5 and 25 mg/ml) were investigated against P. aeruginosa PAO1 using the broth macrodilution method. Results: Minimum inhibitory concentration of AgNPs, L-arginine and AgNPs combined with 25 and 12.5 mg/ml L-arginine was 15.6 μg/ml, 25 mg/ml, 1.9 μg/ml and 3.9 μg/ml, respectively. Minimum bactericidal concentration of AgNPs, L-arginine and AgNPs combined with 25 and 12.5  mg/ml L-arginine was 31.2 μg/ml, 50 mg/ml, 3.9 μg/ml and 7.8 μg/ml, respectively. Conclusion: Our study suggests that AgNPs along with L-arginine can be used as an alternative antibacterial agent against P. aeruginosa, and might be useful for treatment of wound infections. Keywords: Nanoparticles, Arginine, Anti-Bacterial Agents, Pseudomonas aeruginosa.